The Relationship between Nutritional Status and the Incidence of Hypertension in the Elderly at the Working Area of the Lubuk Pinang Health Center, North Bengkulu - Amelia Rinita; Diana Melida; Sjaaf Fidiariani; Harun Harnavi (Postgraduate, University of Mataram, 2023)
Hypertension may occur primarily or is idiopathic. Where the causative factor cannot be identified or can occur secondarily as a result of a particular disease. This study aims to determine the relationship between nutritional status and the incidence of hypertension in the Elderly Work Area of the Lubuk Pinang Health Center, Muko-Muko Regency, North Bengkulu. The type of research used is analytical observational research with a cross-sectional approach. The affordable population in this study was the elderly who were registered for treatment at the Lubuk Pinang Health Center, Muko-Muko Regency, North Bengkulu, with 36 samples using the total sampling technique. Univariate data analysis is presented in frequency and percentage distribution and bivariate analysis using the spearman correlation test and data processing using the computerized IBM SPSS program version 24.0. The results of this study show that the highest age was 60-70 years, namely 28 people (77.8%), and the most gender was female, namely 31 people (86.1%). The most nutritional status was overweight, 15 people each (41.7%), the most hypertension was stage II, namely 25 people (69.4%), and there was a relationship between nutritional status and the incidence of hypertension in the Elderly Work Area of the Lubuk Pinang Health Center, Muko-Muko Regency, North Bengkulu (p=0.031). This research concludes that the highest age is 60-70 years. The most gender is female, the most nutritional status is overweight, the most hypertension is stage II, and there is a relationship between nutritional status and the incidence of hypertension in the Elderly Work Area of the Lubuk Pinang Health Center, Muko-Muko Regency, North Bengkulu